(untitled) (Journal of Information and Communication Technology, 2019)
Service-Oriented Architecture (SOA) is an approach that can be used to integrate different services across the operating system, platform, language, and network which offers some benefits. However, many organizations failed to fully utilize the SOA because the adoption processes are still immature. Therefore, an exploratory study was conducted which aims to investigate the current issues and practices of SOA adoption, the use of maturity levels for assessing the SOA adoption, and the importance of IT and business benefits in the SOA adoption. Thus, the Grounded Theory approach was adapted in the study which involved seven (7) software development companies in Malaysia. In this study, fourteen (14) SOA practitioners with at least three years of experience in the SOA development were interviewed. The collected data was analyzed through three main coding stages which are open, axial and selective coding. The theory emerged from this study reveals the SOA adoption issues, current practices, maturity levels, IT and Business benefits. The study managed to identify five main issues in SOA adoption which are knowledge, infrastructures, costing, readiness, and documentation issues. The study also portrays five practices related to technology, framework, platform, standard, and tools. On the other hand, the results show five IT and business benefits consecutively. The findings from the study have lead to the theories formulation on the SOA adoption which may assist researchers and SOA assessors to continuously improve the quality and maturity of SOA adoption in the future.